Modern aspects of epidemiology of congenital anomalies of development: methodological issues and the translation of research fndings into clinical practice - O. V. Reshetko; K. V. Lutsevich (Качественная клиническая практика, 2019)
Progress achieved in the identifcation and characterization of the risk factors for congenital anomalies occur mainly from epidemiological studies, which gave many associations between risk factors and groups of birth defects. However, in clinical practice the transmission of these associations as the actual reasons remains very difcult. Characteristics and epidemiological analysis of possible factors, including drugs, associated with the occurrence of congenital anomalies, are crucial for the development of prevention activities that have an impact on the incidence of defects. To further reduce the global burden of birth defects can help the integration of studies in epidemiology, genetics and epigenetics through personalized and population oriented preventive strategies.